Student Character Building Model at Muhammadiyyah Al-Kautsar High School PK (Program Khusus) Kartasura - Thufail Afif Abdullah; Nurul Fatimah Nur Mukharomah; Nila Fauzia Yusfa (Walidem Institute and Publishing (WIP), 2023)
The purpose of this study is to reveal the personality of Muhammadiyah Al Qawtsar PK Kartasura High School students. Development of student character through independence and autonomy. The type of research used is qualitative research uses one type of research, namely field research and data collection using interviews with counsellors of SMA Muhammadiyah Al Qawtsar PK Kartasura. Based on the results of the study, the following conclusions were drawn: SMA Muhammadiyah Al-Kawtsar PK Kaltasura. In SMA PK Muhammadiyah, the formulation and implementation of legal regulations, the formation of student disciplinary character, and the implementation of these regulations are carried out by students. Participation: Students make their own school rules. In this case, the class of the committee is representative.